Weather Data for Africa RISING Sites in Ethiopia - International Center for Tropical Agriculture; International Livestock Research Institute (International Food Policy Research Institute, 2018)
Site-specific watershed analysis requires site-specific meteorological data. Due to high spatial and temporal variability nature, collecting in-situ weather data is essential for modeling biophysical processes and understanding the biophysical condition of watersheds. In addition, site-specific weather information by itself is useful for improving agricultural practices in selected Africa RISING sites. This data study contains weather-related data which was generated to support various analysis in Africa RISING sites. The data included all the weather elements i.e. precipitation, soil moisture (volumetric water content, soil temperature, cation exchange capacity (CEC)), wind (direction, speed, and gusts), air temperature, solar radiation, and relative humidity. These data were collected at two sites (kebeles) for each Africa RISING sites. They were collected at 15 minutes interval since September 2014. The data collection is still ongoing.